2021
DOI: 10.1371/journal.pone.0250225
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of service tactic formation on players’ movements and point outcome between national and beginner level padel

Abstract: The aim of this study was to analyze the influence of service tactic formation on players’ movements and point outcome at two different performance levels. The sample contained 2,148 points corresponding to 18 matches from two male padel indoor tournaments. Players were classified according to their game level: high-level (N = 36; age = 33.3 ± 6.9 years) and beginner (N = 36; age = 35.4 ± 6.8 years). Variables pertaining to service tactic formation (conventional or Australian), point outcome and movement patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 48 publications
0
16
0
3
Order By: Relevance
“…A total of 479 padel players with a different level of experience were included in the studies and 1098 matches were also analyzed. Most of the studies are cross-sectional ( n = 3) [ 7 , 10 , 15 ] and observational ( n = 12) [ 3 , 7 , 9 , 12 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]; studies on match analysis utilized the systematic observation of padel match videos from official channels. The current literature argues over four different aspects of padel: match analysis, anthropometric and physical fitness, the biological effects of padel matches on athletes, and the risk of injury and rehabilitative approaches.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 479 padel players with a different level of experience were included in the studies and 1098 matches were also analyzed. Most of the studies are cross-sectional ( n = 3) [ 7 , 10 , 15 ] and observational ( n = 12) [ 3 , 7 , 9 , 12 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]; studies on match analysis utilized the systematic observation of padel match videos from official channels. The current literature argues over four different aspects of padel: match analysis, anthropometric and physical fitness, the biological effects of padel matches on athletes, and the risk of injury and rehabilitative approaches.…”
Section: Resultsmentioning
confidence: 99%
“…The current literature argues over four different aspects of padel: match analysis, anthropometric and physical fitness, the biological effects of padel matches on athletes, and the risk of injury and rehabilitative approaches. Almost all the study included were from Spain ( n = 16) [ 3 , 7 , 9 , 10 , 12 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]; only one was from Sweden [ 26 ]. Ten of the included studies investigated game dynamics [ 3 , 9 , 12 , 16 , 17 , 18 , 19 , 20 , 21 ], of which one [ 12 ] analyzed the court zone involved in the attacking and defensive phase of the match; six studies [ 3 , 16 , 17 , 19 , 20 , 21 ] investigated padel strokes, highlighting that the smash is one of the most effective strokes with which to stop the rally; on the other hand, the lob is the most valid in a defensive position [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, if one offensive player moves close to the net, his partner moves some meters back. Regarding tactic formations, Ramón-Llin [ 75 ] found how high level players used a significantly higher percentage of the Australian formation than beginners, even though it has been reported that serving pairs won a higher percentage of points using traditional tactics instead of the Australian formation [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported differences in distances covered and player's maximum velocity depending on the players level and service tactic formation. 30 In this sense, it was observed that high-level players covered more distance and moved faster than beginners as beginners make more errors and the point duration is lower than high-level players. 56 In addition, service tactic formation had a great influence on these parameters.…”
Section: Discussionmentioning
confidence: 96%